SUMBANGAN PENDIDIKAN AGAMA KATOLIK TERHADAP KEHIDUPAN MENGGEREJA SISWA KATOLIK SMA DAN SMK KATOLIK KOTA MADIUN - Agustinus Supriyadi; Isabella Nastiti Anggraheni (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Based on Matthew 28: 19-20, all people are called to proclaim the Good News includes young Catholics. Young Catholics carry out the mission expressed throughthe implementation of the five tasks of the Church. However, circumstances today give many negative effects for young Catholics. Therefore it is needed an education system in school, especially in the field of growing faith. This is the importance role of the Catholic Religious Education for students to strike the challenges of life in the light of the Christian faith. This scientific research aims to prove contribution of Catholic Religious Education in Catholic senior highschool and vocational school for student Catholic way of living in the church. The results showed that most Catholic student knew the benefits of understanding the Catholic Religious Education and life but not deep. Catholic Religious Education in schools contributes little to the Catholic student life because there are other factors suchaseducation parents, support of the people around themselves (priests, sisters, and mothers orphanage administrators), and their selfawareness.